PENDEKATAN COGNITIVE BEHAVIORAL THERAPY (CBT): LITERATUR REVIEW UNTUK MENGATASI STRES AKADEMIK PESERTA DIDIK - Suprianto Baen; Eka Wahyuni (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The purpose of this research is to find out the causes of academic stress in students and the impact of applying the cognitive behavioral therapy approach to dealing with academic stress. The method used in this study is in the form of a literature review study, articles are searched through the database using Google Scholar is a web search engine run by Google that indexes scientific literature such as journal articles, academic books, conferences, found using the keywords